Analysis of Digital Transformation Challenges in Mediating Accounting Digitalization and Electronic Commerce (E-Commerce) on Technology- Based Entrepreneurship in Micro, Small and Medium Enterprises in Medan City - Mahyudin, Mahyudin; Nazah, Khairatun; Agustina, Agustina (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2025)
Micro, small and medium enterprises are community businesses located in the regional environment in particular and in Indonesia in general, MSMEs are indicators of economic improvement and unemployment reduction that are fostered by many local and central governments. In Medan city, there are 38,343 MSMEs and as many as 1,875 have been registered as MSMEs under the guidance of the Medan City Prindak SME Cooperative Office. The Medan city government encourages business actors to empower digitalization in their business productivity so that it can facilitate running a business and improve their business to a superior level in terms of services and operations. The challenge of business digitalization makes many business people have to relearn about the technology that is suitable for them to apply to their business according to market needs or needs in services or organizations. This approach is able to test a model that is most ideal in estimating endogenous variables. The population in this study were micro, small and medium enterprises located in Medan Marelan sub-district and Medan Belawan sub-district with a total of 278 businesses. sampling using the slovin formula with an error rate (margin of error) of 5% or 0.05 and a confidence level This research was conducted in the Medan City area with the research population being MSME actors located in Medan Marelan sub-district and Medan Belawan sub-district as many as 278 businesses. The sampling method for this study uses the Slovin formula where the error rate is 5% so as to get a population of 164 businesses. After analyzing the research data, a discussion can be made regarding the direct effect that the direct effect produced by the variables of accounting digitalization, electronic commerce, digital transformation challenges is significant on technology-based entrepreneurial challenges, the results of the direct effect of accounting digitalization variables, electronic commerce are significant on digital transformation challenges, the results of the indirect effect of accounting digitalization variables, electronic commerce on technology-based entrepreneurship through digital transformation challenges are significant